The role of the immune system in atherosclerosis: molecules, mechanisms and implications for management of cardiovascular risk and disease in patients with rheumatic diseases - Skaggs, Brian J. (2012)
Rapid-onset cardiovascular disease is a major concern for many patients suffering from SLE. Cardiovascular events are more frequent and occur much earlier in SLE patients compared to healthy controls. Traditional risk factors such as altered lipid levels, older age and smoking do not fully explain the increased risk of cardiovascular disease, strongly suggesting that autoimmunity contributes to accelerated atherosclerosis. Altered immune system function is recognized as the primary contributor to both the initiation and progression of atherosclerosis. Multiple manifestations of autoimmunity, including autoantibodies, altered cytokine levels and innate immunity response, adipokines, dysfunctional lipids, and oxidative stress appear to contribute to atherosclerotic risk. In addition, multiple SLE therapeutics appear to affect the development and progression of atherosclerosis both positively and negatively. SLE-specific biomarkers for identifying patients at risk of developing accelerated atherosclerosis are starting to be identified by multiple groups, and a comprehensive, clinically testable biomarker panel could be invaluable for identifying and treating these patients.